2023
DOI: 10.1097/ju.0000000000003196
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Mucosal Cystitis Cystica Lesions Are Tertiary Lymphoid Tissues That Correlate With Recurrent Urinary Tract Infection Frequency in Postmenopausal Women

Abstract: Purpose:We identify correlates and clinical outcomes of cystitis cystica, a poorly understood chronic inflammatory bladder change, in women with recurrent urinary tract infections.Materials and Methods:A retrospective, observational cohort of women with recurrent urinary tract infections who underwent cystoscopy (n=138) from 2015 to 2018 were identified using electronic medical records. Cystitis cystica status was abstracted from cystoscopy reports and correlations were identified by logistic regression. Urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ligon et al (page 928) in a multi-institutional study explore the association of cystitis cystica and recurrent urinary tract infections (UTIs). 6 In this retrospective, observational cohort of women with recurrent UTIs, the presence of cystitis cystica was associated with a shorter time to next UTI. The authors conclude that identifying these lesions cystoscopically may be useful in informing future UTI risk and personalizing treatment strategies.…”
Section: An Overdue Focus On Urinary Infectionsmentioning
confidence: 81%
“…Ligon et al (page 928) in a multi-institutional study explore the association of cystitis cystica and recurrent urinary tract infections (UTIs). 6 In this retrospective, observational cohort of women with recurrent UTIs, the presence of cystitis cystica was associated with a shorter time to next UTI. The authors conclude that identifying these lesions cystoscopically may be useful in informing future UTI risk and personalizing treatment strategies.…”
Section: An Overdue Focus On Urinary Infectionsmentioning
confidence: 81%
“…5 Research by another group also established a link between the presence of cystitis identified on cystoscopy and increased rUTI frequency. 6 Therefore, if the quiescent reservoirs in the murine model equate to the areas of chronic cystitis persisting in women with uncomplicated rUTI, the next step, should they fail to respond to several short or prolonged antibiotic courses, may be to consider eradicating these sites directly.…”
Section: What If Uti Recurrences Were Due To Persistent Resident Bact...mentioning
confidence: 99%
“…Ligon et al, in their recent report, demonstrate that bladder mucosal cystitis cystica (CC) lesions are tertiary lymphoid tissues/TLSs and most prevalent in women with recurrent (r) urinary tract infection (UTI). 4 In this observational study conducted in a retrospective cohort of 138 women (>18 years) with rUTI, 38% of cases had evidence of CC. Notably, women with CC experienced rUTI with a significantly shorter time to their next UTI.…”
mentioning
confidence: 91%